Metabolomic and lipidomic studies on the intervention of taurochenodeoxycholic acid in mice with hyperlipidemia - Cui, Na; Zhang, Wensen; Su, Fazhi; Zhang, Zhihong; Li, Biao; Peng, Donghui; Sun, Yanping; Zeng, Yuanning; Yang, Bingyou; Kuang, Haixue; Wang, Qiuhong (Frontiers in Pharmacology, 2023)
Bile acids are the main component of animal bile and are directly involved in the metabolic process of lipids in vivo. Taurochenodeoxycholic acid (TCDCA) is the primary biologically active substance in bile acids and has biological functions such as antioxidant, antipyretic, anti-inflammatory, and analgesic activities and improves immunity. In the present study, we assessed the impact of TCDCA on hyperlipidemia development in mouse models. Mice were fed a high-fat diet (HFD) to induce hyperlipidemia and orally administered different doses of TCDCA orally for 30 days. Then, indicators such as triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) in mice were detected. Using HE and ORO staining techniques, the morphology of the mice’s liver tissue was detected. Based on metabolomic and lipidomic analyses, we determined the mechanism of TCDCA in treating hyperlipidemia. The results showed that TCDCA had a significant ameliorating effect on dietary hyperlipidemia. In addition, it exerted therapeutic effects through glycerophospholipid metabolism.